Saint-Venant's Problem for Heterogeneous Elastic Solids - D. Iesan (Engineering Transactions)
This paper gives a method for solving Saint-Venant's problem in the case of inhomogeneous and isotropic elastic cylinders when the elastic coefficients are independent of the axial coordinate. The cross-section of the cylinder is assumed to be occupied by different inhomogeneous and isotropic elastic materials. The problem is then generalized to the case when the cylinder is subjected to body forces and to surface tractions on the lateral surface.